Pituitary Activation by Bacterial Endotoxins in the Rainbow Trout (Salmo gairdneri) - Wedemeyer, Gary (1969)
Endotoxins from Escherichia coli and Aeromonas salmonicida caused marked cortisol production in the rainbow trout (Salmo gairdneri).